Implementasi Program Kartu Identitas Anak (KIA) Melalui Penggunaan Sistem Informasi Administrasi Kependudukan (SIAK) di Pemerintah Kota Cimahi - Raisa Rafifiti Choerunnisa; Rosinta Rosinta (STMIK Budi Darma, 2021)
The results of a study conducted by the Center for the Study of Child Protection (PUSKAPA) at the University of Indonesia noted that 40 million Indonesian children were born without a civil registration, so they do not have a legal identity and have difficulty accessing basic services. The government in protecting and prospering children issued Ministerial Regulation Number 2 of 2016 concerning Child Identity Cards (KIA). The purpose of this study was to determine the implementation of the Child Identity Card program through the use of the Population Administration Information System (SIAK) in the Cimahi City Government and the obstacles encountered in its implementation. Since the existence of the Child Identity Card program, the City of Cimahi has been appointed as one of the first fifty regencies/cities to implement the program. Until now, the implementation of the Child Identity Card program carried out at the Population and Civil Registration Office of Cimahi City has been carried out well. Although in its implementation there are still obstacles. These obstacles are: 1) Lack of public awareness of the City of Cimahi on the importance of having a KIA, 2) Errors in inputting NIK in the SIAK application by operators when printing KIA, 3) Lack of public understanding of service procedures at the Disdukcapil Cimahi City which has switched to online-based services using the website and application of Sipade and Sibenda Cimahi City. After the research has been carried out, the efforts that can be made in order to increase the ownership of KIA in Cimahi City are: 1) Activities to accelerate the issuance of KIA, 2) Re-checking the NIK that has been inputted, 3) Providing understanding to residents about service procedures at the Cimahi City Disdukcapil which has been based on digital.